Fatigue in colorectal cancer patients: prevalence and associated factors Fatiga en pacientes con cáncer cuello rectal: superioridad y factores asociados Fadiga em pacientes com câncer colorretal: prevalência e fatores associados - Dálete Delalibera Corrêa de Faria Mota; Cibele Andrucioli de Mattos Pimenta; Ricardo Caponero (Universidade de São Paulo, 2012)
This study identified the prevalence and predictors of fatigue in colorectal cancer (CRC) patients. Cross-sectional study with 157 adult CRC outpatients (age 60±11.7 years; 54% male; cancer stage IV 44.8%). The Piper Fatigue Scale-revised was used to assess fatigue scores. Socio-demographic, clinical, depression, performance status, pain and sleep disturbance data were assessed. Associations between fatigue and these data were analyzed through logistic regression models. Fatigue was reported by 26.8% patients. Logistic regression identified three predictors: depression (OR: 4.2; 95%CI 1.68-10.39), performance status (OR: 3.2; 95%CI 1.37-7.51) and sleep disturbance (OR: 3.2; 95%CI 1.30-8.09). When all predictors were present, the probability of fatigue occurrence was 80%; when none were present, the probability was 8%. The model's specificity and sensitivity were 81.9% and 58.6%, respectively. Through the assessment of depression, performance status and sleep disturbance, the probability of fatigue occurrence can be estimated, and preventive and treatment strategies can be rapidly implemented in clinical practice. Los objetivos de este estudio fueron la identificación de la superioridad y los predictores de fatiga en pacientes con Cáncer Cuello rectal (CCR). Se trata de estudio seccional con 157 pacientes de ambulatorio con CCR (edad 60±11,7 años; 54% hombres; estadio cáncer IV 44,8%). La Escala de Fatiga de Piper - Revisada fue utilizada para evaluar fatiga. Datos sociodemográficos, clínicos, depresión, funcionalidad, dolor y sueño fueron evaluados. La asociación entre variables fue realizada por regresión logística. Fatiga fue reportada por 26,8% pacientes. Por la regresión logística se identificaron tres predictores: depresión (OR: 4,2; 95%IC 1,68-10,39), funcionalidad (OR: 3,2; 95%IC 1,37-7,51) y perjuicio del sueño (OR: 3,2; 95%IC 1,30-8,09). Cuando todos predictores estaban presentes, la probabilidad de ocurrencia de fatiga fue del 80%; cuando ninguno estaba presente, la probabilidad fue del 8%. La especificidad y sensibilidad del modelo fueron, respectivamente, 81,9 y 58,6%. Conociéndose la probabilidad de fatiga, por medio de la evaluación de depresión, funcionalidad y perjuicio del sueño, se vuelve posible la implementación de estrategias de prevención y tratamiento en la clínica. Os objetivos deste estudo foram identificar a prevalência e os preditores de fadiga em pacientes com Câncer Colorretal (CCR). Trata-se de estudo seccional com 157 pacientes ambulatoriais com CCR (idade 60±11,7 anos; 54% homens; estádio câncer IV 44,8%). A Escala de Fadiga de Piper - Revisada foi utilizada para avaliar fadiga. Dados sociodemográficos, clínicos, depressão, funcionalidade, dor e sono foram avaliados. A associação entre variáveis foi realizada por regressão logística. Fadiga foi reportada por 26,8% pacientes. Pela regressão logística identificaram-se três preditores: depressão (OR: 4,2; 95%IC 1,68-10,39), funcionalidade (OR: 3,2; 95%IC 1,37-7,51) e prejuízo do sono (OR: 3,2; 95%IC 1,30-8,09). Quando todos preditores estavam presentes, a probabilidade de ocorrência de fadiga foi de 80%; quando nenhum estava presente, a probabilidade foi de 8%. A especificidade e sensibilidade do modelo foram, respectivamente, 81,9 e 58,6%. Conhecendo-se a probabilidade de fadiga, por meio da avaliação de depressão, funcionalidade e prejuízo do sono, torna-se possível a implementação de estratégias de prevenção e tratamento na clínica.